2017
DOI: 10.3390/ijerph14030280
|View full text |Cite
|
Sign up to set email alerts
|

Nonfatal Injuries and Psychosocial Correlates among Middle School Students in Cambodia and Vietnam

Abstract: The aim of the study was to estimate the prevalence and psychosocial correlates of nonfatal injury among middle school students in Cambodia and Vietnam. Cross-sectional data from 7137 school children (mean age 15.5 years, SD = 1.4) who were randomly sampled for participation in nationally representative Global School-based Health Surveys (GSHS) in Cambodia and Vietnam were analyzed. The proportion of school children reporting one or more serious injuries in the past year was 22.6% among boys and 17.5% among gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 18 publications
5
18
0
Order By: Relevance
“…Sun (Sun et al 2006) found the occurrence of school injuries that resulted in medical attendance was 5.22% among primary and middle school students in Maanshan City, eastern China. Burn, sprains/fracture and animal bite were top three prevalent injuries, which was consistent with previous studies in Asia (Bhamkar et al 2016;Li et al 2013;Peltzer and Pengpid 2017). More importantly, we found migrant children were more likely to suffer from any unintentional injury and most of the specific injuries.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Sun (Sun et al 2006) found the occurrence of school injuries that resulted in medical attendance was 5.22% among primary and middle school students in Maanshan City, eastern China. Burn, sprains/fracture and animal bite were top three prevalent injuries, which was consistent with previous studies in Asia (Bhamkar et al 2016;Li et al 2013;Peltzer and Pengpid 2017). More importantly, we found migrant children were more likely to suffer from any unintentional injury and most of the specific injuries.…”
Section: Discussionsupporting
confidence: 91%
“…A survey across 7 European regions suggested that mother-reported internalizing problems (scores above the cut-point of emotional problems, hyperactivity, and conduct problems) were associated with (Keyes et al 2014). A possible mechanism for these associations could be a stronger propensity among these children to engage in potentially injury-inducing behavior such as fighting with schoolmates (Peltzer and Pengpid 2017), stimulating in dangerous activities (Steinberg et al 2008), and disregarding public rules. Further, suicide ideation was highly associated with injury incidence, the outcome was also previously found (Peltzer andPengpid 2012, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…“Unintentional injuries are the largest source of premature morbidity and mortality and the leading cause of death among adolescents 10–19 years of age.”1 The South-East Asian region is disproportionally affected by the world’s unintentional injury-related deaths 2. The prevalence of past 12-month serious injuries among adolescents in “Association of Southeast Asian Member States (ASEAN)” was for example, in 20.1% in 2013 Cambodia,3 45.9% in 2008 in Indonesia,4 34.9% in 2012 in Malaysia,5 27.0% in 2007 in Myanmar,4 39.1% in 2003, 54.2% in 2007 and 54.3% in 2011 in the Philippines,6 46.8% in 2008 in Thailand4 and 29.7% in 2013 in Vietnam,3 while it was 40% (median) in “47 low- and middle-income countries.”7…”
Section: Introductionmentioning
confidence: 99%